2020
DOI: 10.1136/bmjopen-2019-035606
|View full text |Cite
|
Sign up to set email alerts
|

Scientific, professional and experiential validation of the model of preventive behaviours at work: protocol of a modified Delphi Study

Abstract: IntroductionTo offer an in-depth understanding of preventive behaviours, those complex behaviours considered as levers to foster work prevention, recent theoretical and empirical studies permitted to develop the model of preventive behaviours at work. The next step is to validate the model with researchers, professionals and workers. This article aims to describe the study protocol that will be used to validate the model of preventive behaviours at work.Methods and analysisThis Delphi Study proposes seven syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
8
0
5
Order By: Relevance
“…Experts were invited to participate by telephone and email. Following recommendations by Lecours et al [ 24 ], the email message contained the following information: principal investigator and research team, description of the study, reasons why the expert was selected, procedure to follow to participate in the panel, estimation of the time required (participation in all stages), and confidentiality. All of the experts who were contacted voluntarily agreed to participate in the study, signed the informed consent form, and confirmed their attendance before the first meeting.…”
Section: Methodsmentioning
confidence: 99%
“…Experts were invited to participate by telephone and email. Following recommendations by Lecours et al [ 24 ], the email message contained the following information: principal investigator and research team, description of the study, reasons why the expert was selected, procedure to follow to participate in the panel, estimation of the time required (participation in all stages), and confidentiality. All of the experts who were contacted voluntarily agreed to participate in the study, signed the informed consent form, and confirmed their attendance before the first meeting.…”
Section: Methodsmentioning
confidence: 99%
“…Multidisciplinary health professionals validated the indicators in three stages. The Delphi panel consisted of 16 validators, consisting of three oncologists, two oncopharmacists, two oncology nurses, two gynecologists, one general medicine physician, one general surgery physician, two clinical pharmacists, and three academic pharmacists ( van Roozendaal and Krass, 2009 ; Thiyagu et al, 2010 ; Lecours, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In order to create such a rubric for global competence, it was necessary to design a robust and consistent research procedure that could ensure a deep validity in the final outcome. The Delphi technique is commonly utilized in the research context and its validity for development of research instruments, such as questionnaires and rubrics, has already been described by Landeta (2006), Manizade and Mason (2011), Ballesteros and Mata (2009), Yeh and Cheng (2015), Peeraer and Van Petegem (2015), Mengual-Andrés et al (2016), and Lecours (2020). For this reason, we involved a large number of experts who took part in a modified Delphi method, as explained in the following section.…”
Section: Methodsmentioning
confidence: 99%